Austria : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2002)
This 2002 Article IV Consultation highlights that after decelerating sharply in 2001, economic growth in Austria is projected to strengthen gradually during 2002, parallel to the expected improvement in the global economic climate. Real GDP growth is projected to average 1 percent in 2002, supported by a recovery in investor confidence and strong competitiveness. Despite the recent increase, the unemployment rate remains one of the lowest in Europe at about 4 percent. The government intends to stick to its fiscal adjustment plan in 2002.